Elaboración de un software para el diseño de riego a presión utilizando el lenguaje Visual Basic. - Freire Serrano, Carlos Daniel (2013)
Elaborating a software to design a system for pressurized irrigation system using Visual Basic as the programming language, there is a purpose to create a technology that makes easier to calculate, design and to analyze the costs of the irrigation systems; with this program the time used to make calculations for this kind of installations will be reduced and the unintentional mistakes made in the calculations as well. This project is contributes to a sustainable handling of water and soil; these parameters are considered in the execution of this thesis, the main objective of this project is: 1) To contribute to the sustainable handling of water and the soil used for agriculture by using the pressurized irrigation system (sprinkler and dripping) using Visual Basic as the informatics tool. 2) Validating the software by making an exposition with the assistance of the students, teachers and related technicians in the design of the irrigation system. 3) Writing down a manual that contains the explanations for the using of the functions of the program and an example its uses. (Users Manual). This program is really simple and offers no difficulty to the user, giving a great handling experience. That’s how RiegoChees (Program’s name) will be the first irrigation program generated by a student of the Universidad Nacional de Loja